2017
DOI: 10.5977/jkasne.2017.23.3.341
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Subjectivity among Nursing Students Regarding Suicide Attempters

Abstract: Purpose: To identify the types and characteristics of subjective structures among nursing students toward individuals who attempt suicide. Methods: A group of 32 third- and fourth-year nursing students with experience in clinical practice rated 35 Q-statements on a nine-point scale according to their opinion. Data analysis was conducted using the PC-Quanl program. Results: Subjectivity among nursing students toward individuals who attempt suicide was analyzed for three types. Type 1 (social responsibility emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…In a previous study, many nurses in Japan reported finding it difficult to understand how to assist suicide attempters or provide proper care (Aoki & Katayama, 2017). In addition, a survey of nursing students in Korea conducted using the Q-strategy showed that educational programs based on the subjectivity of attitudes toward patients who attempt suicide was needed (Cho, Lee, & Park, 2017). This study is a study based on limited the tool and the environment, and there are limits to using the results.…”
Section: Educationmentioning
confidence: 99%
“…In a previous study, many nurses in Japan reported finding it difficult to understand how to assist suicide attempters or provide proper care (Aoki & Katayama, 2017). In addition, a survey of nursing students in Korea conducted using the Q-strategy showed that educational programs based on the subjectivity of attitudes toward patients who attempt suicide was needed (Cho, Lee, & Park, 2017). This study is a study based on limited the tool and the environment, and there are limits to using the results.…”
Section: Educationmentioning
confidence: 99%